Emotions of tutors working in distance education universities during Covid pandemic - Mavroudi, Anna; Papanikolaou, Kyparisia (Συνέδρια της Ελληνικής Επιστημονικής Ένωσης Τεχνολογιών Πληροφορίας & Επικοινωνιών στην Εκπαίδευση, 2024)
The paper is a call for reflection in the post pandemic era focusing on tutors’ sentiment since there is a body of literature suggesting a deterioration of tutors’ psychological well-being. It is a small case study examining the feelings of university tutors’ teaching in distance education universities during the pandemic. It also examines the correlation between tutors’ sentiment (negative, mixed/neutral, positive) and years of teaching experience. Twenty tutors working in two different European Open Universities comprised a diverse sample which answered anonymously to an online survey. The results were analysed using mixed methods. The main results suggest that the majority of tutors felt confident and that there is no correlation between years of experience in distance education and sentiment. The case study contributes to the discussion on how we can future proof higher education institutions for uncertain times, taking into account that tutors are foremost humans and not well-oiled machines